Architecture of African swine fever virus and implications for viral assembly - Wang, Nan; Zhao, Dongming; Wang, Jialing; Zhang, Yangling; Wang, Ming; Gao, Yan; Li, Fang; Wang, Jingfei; Bu, Zhigao; Rao, Zihe; Wang, Xiangxi (Science (American Association for the Advancement of Science), 2019)
African swine fever virus (ASFV) is a giant and complex DNA virus that causes a highly contagious and often lethal swine disease for which no vaccine is available. Using an optimized image reconstruction strategy, we solved the ASFV capsid structure up to 4.1 angstroms, which is built from 17,280 proteins, including one major (p72) and four minor (M1249L, p17, p49, and H240R) capsid proteins organized into pentasymmetrons and trisymmetrons. The atomic structure of the p72 protein informs putative conformational epitopes, distinguishing ASFV from other nucleocytoplasmic large DNA viruses. The minor capsid proteins form a complicated network below the outer capsid shell, stabilizing the capsid by holding adjacent capsomers together. Acting as core organizers, 100-nanometer-long M1249L proteins run along each edge of the trisymmetrons that bridge two neighboring pentasymmetrons and form extensive intermolecular networks with other capsid proteins, driving the formation of the capsid framework. These structural details unveil the basis of capsid stability and assembly, opening up new avenues for African swine fever vaccine development.